The Lost Hamlet of Alwarton: Excavations north of Haverhill, Suffolk - Clarke, Rachel; Graham, Steven; Holder, Nick; Anderson, Sue; Fosberry, Rachel; Foster, Hayley; Timberlake, Simon; Sami, Denis; White, Joshua C.; Brown, David; et al. (Medieval Settlement Research, 2024)
Excavations on the northern edge of Haverhill, Suffolk, revealed an extensive network of enclosures, buildings and tofts/crofts laid out either side of a lane; this is now one of the largest investigations of a rural medieval settlement carried out in the county. Documentary research has provided a name for this long-lost hamlet – ‘Alwarton’, later Alderton – and shown that it may have preceded the establishment of the nearby documented Alderton chapel by many decades, if not centuries.